(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Overweight and obesity are the major health problem in both developed and devloping countries. Various lipid abnormalities are observed in overweight and obese population. The objective of the study to evaluate relationship between postprandial triglycerides with overweight and obesity.The present case control study was carried out in the Department of Biochemistry, Chittagong Medical College. Samples were collected from population of different area of Chittagong City Corporation of different occupations, age from 35-60 years. The data were collected by a structured questionaries. BMI was calculated by standardized protocol.Serum triglycerides was estimated at fasting, 2 hours postprandial and 4 hours postprandial condition and was analyzed in the semi auto analyzer.In the obtained results of this study the mean BMI of female was significantly (p <0.05) higher than that of male. Regarding fasting triglycerides there was a significant difference between values of serum triglycerides of cases and controls (p <0.001) . In respect of postprandial serum triglycerides value the mean value were significantly higher than of controls (p <0.001). Increased serum fasting TG was observed in 73% but increased postprandial serum triglycerides was observed in a higher score, ie, 92% cases in two hours postprandial and 81% cases in four hours postprandial.Study showed that post prandial hypertriglyceridemia was the common lipid abnormality in overweight and obese population. JCMCTA 2016 ; 27 (2) : 67 - 71